Associative hallucinations result from stimulating left ventromedial temporal cortex. (October 2016) - Aminoff, Elissa M.; Li, Yuanning; Pyles, John A.; Ward, Michael J.; Richardson, R. Mark; Ghuman, Avniel S.
Abstract: Visual recognition requires connecting perceptual information with contextual information and existing knowledge. The ventromedial temporal cortex (VTC), including the medial fusiform, has been linked with object recognition, paired associate learning, contextual processing, and episodic memory, suggesting that this area may be critical in connecting visual processing, context, knowledge and experience. However, evidence for the link between associative processing, episodic memory, and visual recognition in VTC is currently lacking. Using electrocorticography (ECoG) in a single human patient, medial regions of the left VTC were found to be sensitive to the contextual associations of objects. Electrical brain stimulation (EBS) of this part of the left VTC of the patient, functionally defined as sensitive to associative processing, caused memory related, associative experiential visual phenomena. This provides evidence of a relationship between visual recognition, associative processing, and episodic memory. These results suggest a potential role for abnormalities of these processes as part of a mechanism that gives rise to some visual hallucinations.